Childhood sexual abuse and early substance use in adolescent girls: the role of familial influences. (1st March 2013) - Sartor, Carolyn E.; Waldron, Mary; Duncan, Alexis E.; Grant, Julia D.; McCutcheon, Vivia V.; Nelson, Elliot C.; Madden, Pamela A. F.; Bucholz, Kathleen K.; Heath, Andrew C.
Abstract: Aim: To assess the extent to which the association between childhood sexual abuse (CSA) and early use of alcohol, cigarettes and cannabis in adolescent girls is mediated by risk factors that tend to cluster in families where CSA occurs. Design: An abridged version of the Semi‐Structured Assessment for the Genetics of Alcoholism (SSAGA) was administered by telephone. Participants: A total of 3761 female twins aged 18–29 (14.6% African American, 85.4% European American). Measurements: CSA experiences and history of substance use were queried in the SSAGA‐based interviews. Findings: After controlling for familial influences on early substance use by including co‐twin early use status in models, separate Cox proportional hazards regression analyses predicting onset of alcohol, cigarette and cannabis use revealed a significant association with CSA. The effect was observed to age 19 years for cigarettes and to age 21 years for cannabis, but was limited to age 14 years or younger for alcohol, with the most pronounced risk before age 10 [hazard ratio (HR) = 4.59; confidence interval (CI): 1.96–10.74]. CSA‐associated risk for initiation of cigarette and cannabis use was also highest in the youngest age range, but the decline with age was much more gradual and the hazard ratios significantly lower (HR: 1.70; CI: 1.13–2.56 for cigarettes and HR: 2.34, CI: 1.57–3.48 for cannabis). Conclusions: Childhood sexual abuse history is a distinct risk factor for use of cigarettes and cannabis, and a very strong predictor of early age at first drink.